Mammalian translation elongation factor eEF1A2: X-ray structure and new features of GDP/GTP exchange mechanism in higher eukaryotes. Issue 20 (17th October 2014) - Crepin, Thibaut; Shalak, Vyacheslav F.; Yaremchuk, Anna D.; Vlasenko, Dmytro O.; McCarthy, Andrew; Negrutskii, Boris S.; Tukalo, Michail A.; El'skaya, Anna V.
Abstract: Eukaryotic elongation factor eEF1A transits between the GTP- and GDP-bound conformations during the ribosomal polypeptide chain elongation. eEF1A*GTP establishes a complex with the aminoacyl-tRNA in the A site of the 80S ribosome. Correct codon–anticodon recognition triggers GTP hydrolysis, with subsequent dissociation of eEF1A*GDP from the ribosome. The structures of both the 'GTP'- and 'GDP'-bound conformations of eEF1A are unknown. Thus, the eEF1A-related ribosomal mechanisms were anticipated only by analogy with the bacterial homolog EF-Tu. Here, we report the first crystal structure of the mammalian eEF1A2*GDP complex which indicates major differences in the organization of the nucleotide-binding domain and intramolecular movements of eEF1A compared to EF-Tu. Our results explain the nucleotide exchange mechanism in the mammalian eEF1A and suggest that the first step of eEF1A*GDP dissociation from the 80S ribosome is the rotation of the nucleotide-binding domain observed after GTP hydrolysis.